Perlindungan Hukum Terhadap Anak Sebagai Pelaku Tindak Pidana Dalam Sistem Peradilan Pidana Anak di Indonesia - Pedro Sutanto; R. Rahaditya (UNES Law Review, 2024)
Children are very important for human survival and the survival of a country or nation. Children experience very important changes as they grow and develop. Starting from birth and continuing until puberty, childhood is marked by the process of exploring a child's identity. Children during puberty often commit deviant acts or crimes without realizing it. the majority of children who commit crimes without intending to cause harm do not receive adequate and comprehensive legal protection. So it is necessary to protect children who are perpetrators of criminal acts. The research method used in the research is Normative Juridical research. The primary data sources used in normative research are those contained in statutory regulations and other statutory regulations. In normative studies, library research is used to collect data. The data collected was tested through qualitative analysis. This research examines normative or legal variables through the use of descriptive analysis techniques, which include providing descriptive explanations for the data obtained, connecting various pieces of evidence, and drawing inductive conclusions. Legal protection for children as perpetrators of criminal acts in the juvenile criminal justice system in Indonesia is contained in Law no. 11 of 2012 concerning the Juvenile Justice System which aims to protect children who commit criminal acts. Children who commit crimes are given protection at every opportunity in the juvenile criminal justice system. starting from the arrest, detention stage, investigation stage, prosecution, trial stage as well as during the coaching period.